1998
DOI: 10.1097/00003072-199805000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Double-Phase Tc-99m Sestamibi Scintigraphy in the Preoperative Location of Lesions Causing Hyperparathyroidism

Abstract: Hyperparathyroidism (HPT) is one of the most prevalent endocrine diseases, for which the only effective treatment is surgery. The use of imaging techniques in the preoperative localization of the hyperfunctioning glands is the subject of controversy. The purpose of this paper is to assess the use of double-phase scintigraphy with Tc-99m sestamibi in the localization of lesions causing HPT. We used scintigraphy to preoperatively examine 41 patients, 31 of whom had primary HPT and 10 with secondary HPT. We acqui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0
2

Year Published

2000
2000
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(21 citation statements)
references
References 24 publications
1
18
0
2
Order By: Relevance
“…However, sensitivity is influenced by the size of lesions, which is a significant feature for diagnosis in young children. For Jones et al [8], the sensitivity was 92% for lesions of up to 500 mg, moreover it was 50% for lesions smaller than 500 mg, and had a better sensitivity for detecting adenomas (92%) and hyperplasias (62%) as reported by Blanco et al [9]. …”
Section: Discussionmentioning
confidence: 89%
“…However, sensitivity is influenced by the size of lesions, which is a significant feature for diagnosis in young children. For Jones et al [8], the sensitivity was 92% for lesions of up to 500 mg, moreover it was 50% for lesions smaller than 500 mg, and had a better sensitivity for detecting adenomas (92%) and hyperplasias (62%) as reported by Blanco et al [9]. …”
Section: Discussionmentioning
confidence: 89%
“…Different techniques were used in performing PT scintigraphy, both with 99m Tc-sestamibi alone (12,29,30) and 99m Tc-sestamibi in conjunction with 123 I or 99m Tcpertechnetate for thyroid image subtraction (9,26,27), with similar results. Dual phase imaging with single-photon emission computer tomography (SPECT) seems to be a promising procedure for the detection of hyperfunctioning PT tissue, both increasing the sensitivity of 99m Tc-sestamibi scintigraphy and appearing particularly useful in localizing mediastinal glands (38,39).…”
Section: Discussionmentioning
confidence: 90%
“…This methodology requires 2 sets of images, one at 5-15 min (early) and one at 2-3 h (delayed). Investigations have reported good results (11,16,17), similar in accuracy to the subtraction method, although few direct comparison studies have been reported (18)(19)(20).…”
mentioning
confidence: 92%